Interactions of extracts from selected chewing stick sources with Aggregatibacter actinomycetemcomitans - Kwamin, F.; Gref, R.; Haubek, D.; Johansson, A. (My University, 2012)
AbstractBackgroundAggregatibacter actinomycetemcomitans produces a leukotoxin that activates a pro-inflammatory death of human monocytes/macrophages. A specific clone of this bacterium (JP2) has a 530-base pair deletion in the leukotoxin promoter gene and significantly enhanced expression of leukotoxin. This specific clone of A. actinomycetemcomitans is common in some African populations and has a strong association with periodontal attachment loss in adolescents in these populations. Chewing sticks of plant origin are commonly used as oral hygiene tool in Africa, but their role as a therapeutic agent in periodontal disease is poorly investigated.ResultsEthanol extracts were made from 7 common plants used as chewing sticks in West-Africa. None of the tested extracts inhibited growth of A. actinomycetemcomitans. However, extracts from Psidium guajava (Guava) completely neutralized the cell death and pro-inflammatory response of human leukocytes induced by the leukotoxin. None of the six other tested chewing stick extracts showed this effect.ConclusionsThe discovery that extracts from Guava efficiently neutralizes A. actinomycetemcomitans leukotoxicity might lead to novel therapeutic agents and strategies for prevention and treatment of aggressive forms of periodontitis induced by infections with the highly leukotoxic JP2 clone of this bacterium.